Development of a simplified diagnostic indicators scoring system and validation for peptic ulcer perforation in a developing country - Suriya C. (2014)
Objective: To perform and confirm a simplified diagnostic indicators scoring system for predicting peptic ulcer perforation (PUP). Methods: A case-control study was conducted including 812 consecutive patients with PUP from retrospective medical records. Each diagnostic indicator measurable at the time of admittance was analyzed by a multiple regression. Stepwise logistic regression was applied with backward elimination of statistically significant predictors from the full model, with P ≥ 0.05 for exclusion. The item scores were transformed from regression coefficients and computed to a total score. The risk of PUP was interpreted using total scores as a simple predictor. This system was internally validated in 218 consecutive patients and compared to existing systems. Results: A PUP risk score was determined from the diagnostic indicators associated with PUP: gender, age, nonsteroidal antiinflammatory drugs used, history of peptic ulcer, intense abdominal pain, guarding, X-ray free air positive, and referral from other hospitals. Item scores ranged from 0-6.0 and the total score ranged from 0-34.0. The area under the receiver operating characteristic curve shows that there was 91.73% accuracy in the total scores predicting the likelihood of PUP. The likelihood of PUP among low risk (scores < 10.5), moderate risk (scores 11-21), and high risk (scores ≥ 21.5) patients was 0.13, 11.44, and 1.95, respectively. Conclusion: This scoring system is an effective diagnostic indicator for identifying the complex cases of PUP. It is a simple system and can help guide clinicians, providing them with a more efficient way to accurately subgroup patients while also reducing potential biases. © 2012 Suriya et al, publisher and licensee Dove Medical Press Ltd.